1992
DOI: 10.7164/antibiotics.45.1626
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acyl-CoA: Cholesterol acyltransferase activity by cyclodepsiptide antibiotics.

Abstract: The effect was studied of the fungal cyclodepsipeptide antibiotics beauvericin and seven distinct enniatins on acyl-CoA: cholesterol acyltransferase (ACAT) activity. In an enzymeassay using rat liver microsomes, all the compounds were found to inhibit ACATactivity. The drug concentration that caused 50%inhibition (IC50 value) of the enzyme activity was determined to be 3.0/jm for beauvericin, indicating that the compoundis one of the most potent ACATinhibitors of microbial origin. Enniatins exhibited much high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(75 citation statements)
references
References 19 publications
1
74
0
Order By: Relevance
“…1 Beauvericin and related fungal cyclooligomer depsipeptides, enniatins, were also reported as inhibitors of acyl-CoA: cholesterol acyltransferase (ACAT) 2 and the human immunodeficiency virus type-1 integrase. 3 Beauvericin was first described from an entomopathogenic fungus Beauveria bassiana on the basis of its toxicity to brine shrimp.…”
Section: Introductionmentioning
confidence: 99%
“…1 Beauvericin and related fungal cyclooligomer depsipeptides, enniatins, were also reported as inhibitors of acyl-CoA: cholesterol acyltransferase (ACAT) 2 and the human immunodeficiency virus type-1 integrase. 3 Beauvericin was first described from an entomopathogenic fungus Beauveria bassiana on the basis of its toxicity to brine shrimp.…”
Section: Introductionmentioning
confidence: 99%
“…(antimalarial (16)), and the microbial metabolites tryptanthrin (10, antibiotic (17)), fumiquinazolines A ( l l ) , B (12), and C (13) (cytotoxic agents ( 1 8) The enniatin metabolites are known to exhibit insecticidal (21,22), antibiotic (23), and phytotoxic activities (24), and to also inhibit cholesterol biosynthesis (25). In this work, the antagonistic effect of F .…”
Section: Resultsmentioning
confidence: 99%
“…32 In this sense, verticilides might represent potential leads beyond the pyripyropenes, although their ACAT2 selectivity is insufficient. We previously reported that two types of depsipeptides, beauveriolides and beauvericin, had ACAT inhibitory activity 25,33 and investigated their selectivity toward the two isozymes. Beauveriolides I and III were more selective toward ACAT1, while beauvericin inhibited both ACAT1 and ACAT2.…”
Section: Inhibition Of Cholesteryl Ester (Ce) Synthesis In Acat1-and mentioning
confidence: 99%
“…One was identified as verticilide (verticilide A1 in this study), which had previously been reported to have insecticidal activity, 20,21 but the others were new compounds, named verticilides A2, A3 and B1 ( Figure 1). They are members of the cyclodepsipeptide family such as beauveriolides, [22][23][24] beauvericin, 25 enniatins 26 and bassianolide. 27 In this study, the taxonomy of the producing strain, fermentation, isolation, structure elucidation and biological properties of verticilides are described.…”
Section: Introductionmentioning
confidence: 99%